What Do We Know about the Effectiveness of Leniency Policies? A Survey of the Empirical and Experimental Evidence - Catarina Marv\~ao; Giancarlo Spagnolo (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2014)
Over the last decade a large body of economic research has emerged that has sought to empirically test the effectiveness of leniency policies as tools to enhance the detection, prosecution and deterrence of cartel conduct. This research has considerable potential value in assisting competition authorities design optimal policies by having a better understanding of the impact that such policies, their specific features and manner of administration, have on the behaviour of cartel participants. Some researchers have taken the approach of testing empirically the effects of actual policies – predominantly those administered by the United States Department of Justice (USDOJ) and the European Commission (EC) – while others have tested different hypothetical policies in the lab. This section reviews the key studies which have been undertaken to date, it highlights the main findings and compares their results. After appreciating the main contributions and limitations of these studies, it concludes with a general assessment and an agenda for future research.
Keywords: D43; K21; K42; L13; L40; L51; 330; Cartels; competition policy; Leniency Programme